Understanding Post-HIPC Public Sentiment: An Empirical Study of Economic Expectations and Fiscal Perception in Somalia - Ali, Ali Yassin Sheikh; Jama , Ahmed Khadar Abdi (International Journal of Economics and Financial Issues, 2025)
In December 2023, Somalia attained the Completion Point under the Heavily Indebted Poor Countries (HIPC) Initiative, leading to 4.5 billion in debt relief and a decrease in foreign debt from over 64% of GDP in 2018 to under 6%. This fiscal milestone signifies a significant achievement in macroeconomic reform and international relations; nonetheless, the perceptions of Somali individuals regarding the effects of debt relief and their aspirations for the post-HIPC economic environment remain ambiguous. This study analyzes public perceptions of the debt relief process and explores how institutional trust, information accessibility, and political narratives influence household expectations on inflation, employment, domestic production, and investment. The research employed a cross-sectional survey methodology and collected data from 500 participants throughout Somalia’s federal member states with a constructed questionnaire based on Expectation Theory, Fiscal Illusion Theory, and Public Choice Theory. The data were examined employing various inferential statistical methods, including exploratory factor analysis (EFA), Pearson correlation, multiple linear regression, moderation analysis, independent samples t-tests, and one-way ANOVA to evaluate relationships, predictive power, and group disparities across significant demographic categories. The results indicate a disjointed and ambiguous impression of the HIPC accomplishment. Increased understanding of the debt relief process significantly correlates with economic optimism; however, this optimism is further amplified by prevalent misconceptions regarding public borrowing and overblown expectations of the effects of debt relief. Trust in government, while not a direct predictor, substantially influences the relationship between awareness and optimism. Political narrative influence exhibits a significant negative correlation with optimism, underscoring distrust regarding governmental communication. Regional differences are pronounced: educated and positive perspectives are prevalent in Puntland and Somaliland, but skepticism and risk perceptions prevail in Southwest and Hirshabelle. Policy proposals encompass the establishment of transparent fiscal accountability systems akin to Uganda’s Virtual Poverty Fund, the initiation of targeted fiscal literacy initiatives, the depoliticization of economic communication, and the involvement of citizens in participatory government. These techniques are crucial for converting debt relief into concrete public trust and comprehensive recovery. Somalia’s situation provides valuable insights for other post-HIPC nations, emphasizing the necessity of reinforcing economic advancements through trust cultivation, transparent communication, and fair reform execution.